Learning the Nuclear : Educational Tourism in (Post)Industrial Sites. - Mazeikienė, Natalija (Frankfurt a.M. : Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2021)
The book illuminates the educational potential of nuclear tourism that becomes a site of outdoor and place-based education, promotes STEM, energy literacy, critical thinking, and environmental skills.
Methodology -- Findings -- Dominating Topics of Virtual Nuclear Education Empirical Research -- Educational Gaming to Explore and Analyze Real-Life Issues -- Virtually Enhanced Touring to Engage and Interact with New Knowledge -- Geolocation Technologies of Virtual Tours Development -- Discussion and Conclusions -- Limitations -- References -- Odeta Norkutė, Natalija Mažeikienė: Energy Literacy in Geography Curriculum: Redefining the Role of Nuclear Power in Changing Energy Landscapes -- Introduction -- A New Role of Geography in Teaching and Learning Energy Literacy and Promoting Education for Sustainability -- Energy Geography in the Curriculum of the Future and Survival -- The Changing Energy Landscape as the Main Concept of Energy Geography -- A New Pedagogy and Active Methods in Addressing Pedagogical Challenges and Overcoming Difficulties in Teaching Energy Geographies -- Teaching About Nuclear Energy: Enhancing Energy Literacy and Scientific Literacy -- Energy Literacy and Energy Issues in the National Curriculum of Geography in Lithuania -- The Concept of Nuclear Energy in Lithuanian Textbooks on Geography -- The Concept of Nuclear Energy in Forms 9-10 -- Identification of the Significance of Nuclear Industry -- Revealing the Role of Nuclear Energy in the World -- Revealing the Threats of Nuclear Energy -- Review of the Situation of Nuclear Energy in Lithuania -- The Concept of Nuclear Energy in Forms 11-12 -- Social and Urban Aspects of Nuclear Energy -- Militaristic Aspects of the Use of Nuclear Energy -- Scientific and Technological Progress and Nuclear Energy -- Generalisation on the Explanation of Nuclear Energy in the Textbooks for Forms 10-12 -- Conclusions -- References -- List of Figures -- List of Tables -- About the Authors -- Series Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books